2012
DOI: 10.1002/mrm.24258
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of venous vessel size in human brain in response to hypercapnia and hyperoxia using magnetic resonance imaging

Abstract: Hypercapnia and hyperoxia give rise to vasodilation and vasoconstriction, respectively. This study investigates the influence of hypercapnia and hyperoxia on venous vessel size in the human brain. Venous vessel radii were measured in response to hypercapnia and hyperoxia. The venous vessel radii were determined by calculation of the changes in R2* and R2 that are induced by breathing 6% CO2 or pure oxygen. The experimental paradigm consisted of two 3‐min intervals of inhaling 6% CO2 or 100% O2 interleaved with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…
Figure 6.(a) A group-level analysis of the regional correlations between viscosity and perfusion changes due to hypercapnia revealed a highly significant positive correlation ( r = 0.2 ± 0.5, t = 3.5, p = 0.002). (b) The MRE-measured viscosity changes Δ ϕ correlated well with blood viscosity changes Δη lit predicted by the Fåhræus–Lindqvist model 40 and regional microvessel diameter data from the literature 43 ( r = 0.64, p = 8.0 × 10 −4 ). CBF: cerebral blood flow.
…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…
Figure 6.(a) A group-level analysis of the regional correlations between viscosity and perfusion changes due to hypercapnia revealed a highly significant positive correlation ( r = 0.2 ± 0.5, t = 3.5, p = 0.002). (b) The MRE-measured viscosity changes Δ ϕ correlated well with blood viscosity changes Δη lit predicted by the Fåhræus–Lindqvist model 40 and regional microvessel diameter data from the literature 43 ( r = 0.64, p = 8.0 × 10 −4 ). CBF: cerebral blood flow.
…”
Section: Resultssupporting
confidence: 64%
“…42 We assumed a standard hematocrit level of H = 45% 40 while values for the vessel diameter D in equation (2) under hypercapnic and normoxic conditions were taken from Shen et al. 43 who approximated normoxic diameters as the average diameters of hyperoxia and hypercapnia for all AAL atlas regions. We furthermore used these D values to calculate the perfusion pressure gradient by normalizing CBF to vessel area as detailed in our recent work.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on isolated cerebral arterioles have shown that application of cocaine or its metabolites induced vasoconstriction, documenting a direct effect of cocaine on blood vessels (He et al, 1994). Most studies of vasoconstriction of cerebral vessels report on diameter reductions of arterial vessels, but previous studies have also shown that venous vessels undergo vasoconstriction (Shen et al, 2013). In the present study, the cocaine-induced diameter decreases were observed across different types and sizes of vessels, including arteries, veins, arterioles and venules.…”
Section: Discussionmentioning
confidence: 99%
“…Bolus imaging provides a faster ΔR 2 and ΔR 2 * measurement. Simultaneous gradient‐echo spin‐echo EPI or spiral sequences are performed with a high temporal resolution similarly to DSC experiments . R 2 and R 2 * weighted images are acquired before, during and after the CA injection.…”
Section: Principlesmentioning
confidence: 99%
“…Using deoxyhemoglobin as CA, Jochimsen and Möller measured the changes in R 2 and R 2 * during a functional challenge (visual task) at 3T and from these, estimated the changes in venous mVD for each activated voxel. More recently, the same team and Shen et al used gases as the CA , with either CO 2 ‐ or O 2 ‐induced BOLD effects to map the venous vessel size of the whole brain. In these conditions, Δχ was found to be lower than with injectable CA, thus limiting the sensitivity of these approaches.…”
Section: Validation Studiesmentioning
confidence: 99%